alpha-Galactosylceramide protects swine against influenza infection when administered as a vaccine adjuvant - Artiaga, B. L.; Yang, G.; Hackmann, T. J.; Liu, Q. F.; Richt, Juergen A.; Salek-Ardakani, S.; Castleman, W. L.; Lednicky, J. A.; Driver, J. P. (My University, 2016)
Natural killer T (NKT)-cells activated with the glycolipid ligand a-galactosylceramide (alpha-GalCer) stimulate a wide array of immune responses with many promising immunotherapeutic applications, including the enhancement of vaccines against infectious diseases and cancer. In the current study, we evaluated whether alpha-GalCer generates protective immunity against a swine influenza (SI) virus infection when applied as an intramuscular vaccine adjuvant. Immunization of newly weaned piglets with UV-killed pandemic H1N1 A/California/04/2009 (kCA04) SI virus and alpha-GalCer induced high titers of anti-hemagglutinin antibodies and generated virus-specific T cells that localized in intrapulmonary airways and in alveolar walls. Vaccination with alpha-GalCer resulted in a systemic increase in NKT-cell concentrations, including in the respiratory tract, which was associated with complete inhibition of viral replication in the upper and lower respiratory tract and much reduced viral shedding. These results indicate that NKT-cell agonists could be used to improve swine vaccine formulations in order to reduce the clinical signs of SI infection and limit the spread of influenza viruses amongst commercial pigs.
Citation: Artiaga, B. L., Yang, G., Hackmann, T. J., Liu, Q. F., Richt, J. A., Salek-Ardakani, S., . . . Driver, J. P. (2016). alpha-Galactosylceramide protects swine against influenza infection when administered as a vaccine adjuvant. Scientific Reports, 6, 13. doi:10.1038/srep23593
Keywords: Invariant Nkt Cells; Killer T-Cells; A Virus-Infection; C-Galactosylceramide; Immune-Responses; Antigen